LIFECYCLE CHALLENGE: MENINGKATKAN KETERAMPILAN KOMUNIKASI BERBASIS GAME EDUKASI DALAM PEMBELAJARAN IPAS KELAS IV - Asa Qolbyatin, Nur; Julianto; Ceffiriana, Paramita; Sunariyah; Hidayati, Fitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the communication skills of class IV students in Natural and Social Sciences (IPAS) subjects using the educational game "Lifecycle Challenge". The Classroom Action Research (PTK) method was carried out in two cycles, with the participation of 28 students. Data was collected using observation sheets. The research results showed a significant increase from the pre-cycle with students' initial completeness of only 39.29% increasing to 78.57% completeness in cycle 1, and 89.29% in cycle 2. This increase confirms the effectiveness of the "Lifecycle Challenge" in developing students' communication skills. Research recommends educational games as an alternative strategy in science learning and recommends further exploration in a broader context.